Effects of urban sprawl due to migration on spatiotemporal land use-land cover change: a case study of Bartın in Türkiye - Şen, Gökhan (Springer Science and Business Media LLC, 2025)
Rapid urban growth is a subject of worldwide interest due to environmental problems. Population growth, especially migration from rural to urban areas, leads to land use and land cover (LULCC) changes in urban centres. Therefore, LULCC and urban growth analyses are among the studies that will help decision-makers achieve better sustainable management and planning. The objective of this study was to ascertain the impact of urbanization, which resulted from migration, on the alterations in LULCC, with a particular focus on the changes in forest areas surrounding the Bartın city centre between 2000 and 2020. Spatial databases for two periods were used to determine changes in urban growth. The spatial and temporal LULCC patterns of land use were quantified by interpreting spatial data. Remote sensing (RS) and geographical information systems (GIS) have been used for data collection, analysis, and presentation. The LULCC was assessed under nine classes using optical remote sensing methods on stand-type maps created from aerial photos. To determine how urban growth affects LULCC, land use status and transition matrices were created for each of the five sprawl zones around Bartın city. The annual change in forest areas is determined by the "annual forest rate". The results indicate that the urbanization of Bartın city from 2000 to 2020 increased by approximately 19% (2510645.82 m2). However, this did not harm the forests; cover increased by 10.32% (174729.65 m²) over the same period. The process of urbanization was particularly evident in open areas and agricultural zones. During this period, there was a 37% reduction in agricultural areas (2943229.85 m²) and a 59% reduction in open areas (1265457.76 m²). The sprawl of Bartın city can be attributed to changes in its demographic structure, which mainly includes the migration of the rural population to urban areas and the emergence of new job opportunities. Factors such as challenging urban living conditions, insecure environments because of the increase in temporary foreign asylum seekers, and retirees returning to their hometowns are believed to have contributed to this population growth.
Keywords: Spatiotemporal analysis; Science; Q; R; Medicine; Environmental monitoring; Remote sensing; Landuse/land cover change; Urban forest; Urban sprawl; Article